(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This research examines the interrelationship between translation impact, ideological frameworks, and technological advancements in contemporary translation studies. The study explores how translation practices are shaped by and simultaneously shape ideological perspectives, while analyzing the transformative role of emerging technologies in the translation process. The research investigates theoretical foundations, practical applications, and future implications of these interconnected dimensions.